A Study of the Effectiveness of Using Sexual Appeals In-store in the Fashion Industry - Chuan, Su Wen (2012)
ABSTRACT Sexual appeal is one of the most common and widely used strategies in mainstream consumer advertising. The use of sexual appeals in advertisements seems to be increasingly popular today. Upon the effectiveness of sexual appeals elicit, an apparent fashion retail store has started to adopt this strategy and communicated in-store using posters and also decorative female and male models. However, there is lack of academic literature on sexual appeals being communicated in a physical store environment using models to attract attention, despite the growing trend. Therefore, this research aims to provide a holistic view of effectiveness of using sexual appeals in the fashion store as a medium. The research uses literature from advertising context and examined if similar results can be produced in a store medium. In-depth interview and focus group interviews are used to generate detailed information and responses. Findings showed that the use of decorative female models in suggestive dressing as in-store sexually appeal do creates initial attention. However, attitude towards the store, the brand and behavioral intentions varies by gender of respondents and at time individuals.